(untitled) (Baghdad Science Journal, 2025)
This study was conducted in Diyala province for renal failure patients during the periods August 2015 - April 2016. Hundred renal failure patients were enrolled in the study after diagnosis by the consultant physician at Ibn-Sina Center for Dialysis in Baquba Teaching Hospital according to criteria adopted by the World Health Organization for diagnosis of renal failure disease. The number of males in patient’s sample was 61 (61%) and females was 39 (39%) with an age range of 10 – 88 year (44.7 ± 22.1 year). In addition, the study included 50 apparently healthy individuals and considered as a group control, in which the number of males and females was similar (25 individual), with an age range of 18 – 88 year (51.7 ± 17.3 year). The results a highly significant decrease serum level of immunoglobulins (IgG and IgM) and complement proteins (C3 and C4) in renal failure patients compared to controls (p ? 0.001). The results showed further a highly significant increased serum level of interleulin-18 in patients compared to controls (p ? 0.001). Interleukin-6 serum level was also increased in patients compared to control, but the difference was not significant (p > 0.05).